Общая теория магнитотермоупругости тонких оболочек - С. О. Саркисян (National Academy of Sciences of Armenia)
В данной работе формулируются предположения (гипотезы), имеющие асимптотическое подтверждение, и на их основе построена общая уточненная прикладная-двумерная теория магнитотермоупругости электро- и теплопроводящих неферромагнитных тонких оболочек, при которой полностью учитываются сдвиговые деформации в оболочке. The present paper provides asymptotically grounded hypotheses, on the basis of which the general specified applied-two-dimensional theory of magnetothermoelasticity of electro- and thermoconducting non-ferromagnetic thin shells is constructed. In case of this theory the shift deformations in the shell are completely taken into account.. Աշխատանքում ձևակերպվում են ընդունելություններ (վարկածներ), որոնք ունեն ասիմպտոտիկ հիմնավորում, և նրանց հիման վրա կառուցված է էլեկտրա- և ջերմահաղորդիչ ոչ ֆերոմագնիսական բարակ թաղանթների ընդհանուր ճշգրտված կիրառական-երկչափ տեսությունը, որի շրջանակներում լիովին հաշվի են առնված թաղանթում սահքային դեֆորմացիաները:
Keywords: Mechanics of deformable solids; Generalities, axiomatics, foundations of continuum mechanics of solids; Coupling of solid mechanics with other effects